Cerebellar Ischemic Stroke Secondary to Rotational Non-Dominant Vertebral Artery Occlusion (RVAO): A Rare Complication Following Supratentorial Surgery - Bono, Beatrice C; Riva, Marco; Pessina, Federico (Asian Journal of Neurosurgery, 2023)
Non-traumatic vertebrobasilar stroke syndrome is rare. Many etiological mechanisms have been described over the years, with the dynamic occlusion of one vertebral artery following head rotation (RVAO) being one of them. We report the case of a patient undergoing surgery for supratentorial metastasis, who postoperatively developed a cerebellar ischemic stroke secondary to RVAO. Postoperative imaging showed a right hypoplastic VA; so, a transient occlusive mechanism was thought to be responsible for the postoperative cerebellar stroke. Although rare, RVAO can occur following head rotation during patient positioning for neurosurgical procedures.
Keywords: complications; ischemia; neurosurgery; rotational vertebral artery occlusion; stroke